191k views
4 votes
68. Find the average rate of change of f(x) = – 3x^2 + 5 from 3 to 7Number 68 on picture

68. Find the average rate of change of f(x) = – 3x^2 + 5 from 3 to 7Number 68 on picture-example-1
User MrFusion
by
4.7k points

1 Answer

2 votes

So, we want to find the average rate of change of:


f(x)=-3x^2+5

From 3 to 7.

First, remember that the average rate of change of a function f(x) from a to b, can be found using the following formula:


A=(f(b)-f(a))/(b-a)

Where:

f(b) is the value of the function at the point b.

f(a) is the value of the function at the point a.

b is the final point

a is the initial point.

In our problem, we're given that:


\begin{gathered} a=3 \\ b=7 \\ f(a)=-3(3)^2+5\to-3(9)+5\to-27+5=-22 \\ f(b)=-3(7)^2+5\to-147+5\to-142 \end{gathered}

Now, let's just replace these values in the previous formula:


A=(-142-(-22))/(7-3)=(-142+22)/(4)=(-120)/(4)=-30

Therefore, the average rate of change is -30.

exercise:

Find the average rate of change of f(x):


f(x)=-2x^2+1

From 4 to 6.

User Peon The Great
by
4.6k points